Weed and nitrogen management effects on weed suppression, soil properties and crop productivity in a maize (Zea mays) - wheat (Triticum aestivum) cropping system under conservation agriculture - OYEOGBE, A I; DAS, T K; RANA, K S; PAUL, SANGEETA; BANDYOPADHYAY, K K; BHATIA, ARTI; SINGH, SHASHI BALA; RAJ, RISHI (The Indian Journal of Agricultural Sciences, 2018)
Weeds and nutrients, particularly N, are two crucial aspects of conservation agriculture (CA), whose management often poses challenge. The combined effects of weed and N management have hardly been studied under CA. This experiment was undertaken to evaluate their effects on weed suppression, soil properties and productivity in a maize (Zea mays L.) – wheat (Triticum aestivum L. emend Fiori & Paol) system under conservation agriculture during 2013-14 and 2014-15. Three weed control treatments as main plots and four nitrogen levels as sub-plots treatments were based on integrated weed management, soil test and plant sensor–GreenSeeker (GS)-aided approach. It was observed that the herbicide combination (atrazine + pendimethalin) and the brown manuring + 2,4-D weed management in maize resulted in 66% and 31% weed control index, respectively over weedy check. But, in wheat, clodinafop-propargyl + carfentrazone-ethyl (post-emergent) and pendimethalin + carfentrazone (pre-emergent) resulted in 81% and 58% weed control index, respectively. The mean maize grain and stover yields were increased by 12% and 8%, respectively due to the optimised GS–N treatments (N2, N3, and N4) than entire N basal application (N1). Also, mean wheat grain and straw yields increased by 9% and 8%, respectively over whole N basal application. The ‘best optimised’ GS–N (N2– 50% basal + 25% broadcast at 25 DAS + rest N guided by GS) had 6%, 7% and 15% greater mean weight diameter, saturated hydraulic conductivity and microbial biomass carbon over whole N basal application after two years of cropping. While brown manuring (maize) + herbicide combination (wheat) had 4%, 7% and 6% greater mean weight diameter, saturated hydraulic conductivity and microbial biomass carbon, respectively over herbicide combinations alone. Available N, P, and K in soil were 8%, 11% and 2% higher in the optimised GS–N treatments over entire N applied as basal. It may be concluded that the integration of brown manuring (in maize)+ herbicide combinations (in wheat), and the optimisation and synchronisation of N fertilisation can suppress weeds, enhance soil fertility with improved maize and wheat productivity.